Perlindungan Hukum Dan Keadilan Para Pihak Melalui Ex Officio Hakim Dalam Putusan Verstek Perkara Perceraian - Abdul Jamil; Muliadi Nur (Jurnal Hukum IUS QUIA IUSTUM, 2022)
Examination of divorce cases should present both husband and wife before the court so that their statements can be heard and peace can be sought. However, the empirical reality of the settlement of divorce cases by judges in the Religious Courts (PA) are generally decided by verstek and have even dominated the number of divorce decisions in several regions in Indonesia. The issue of the verstek decision in divorce cases will eventually result in the loss of the wife's rights because the husband was never present at the trial. Furthermore, the wife would find it difficult to sue for a living for herself and her children. This normative research examines the paradigm of legal protection and justice of the parties in the settlement of divorce cases and the application of ex officio judges as a form of legal protection and justice in verstek decisions in divorce cases. The study was conducted using a statutory and conceptual approaches. Data collection is done by literature study and document study. The results of the study conclude: first, protection of law and justice is the ex officio authority of judges because their position is to assist justice seekers to obtain justice effectively and efficiently through the judicial process. Second, the application of ex officio judges as a form of legal protection and justice in the verstek decision on divorce cases is by adjudicating outside the petitum (ultra petita) in the form of adding an unsolicited order in the petitum as stipulated in Article 41 letter c of Marriage Law No. 1 of 1974 in conjunction with Law No. 16 of 2019. Key Words: Legal protection; justice; ex officio; divorce by verstek Abstrak Pemeriksaan perkara perceraian seharusnya menghadirkan suami dan istri di persidangan untuk dapat didengar keterangannya dan diupayakan perdamaian. Namun, realitas empirik penyelesaian perkara perceraian oleh hakim di Pengadilan Agama (PA) umumnya diputuskan secara verstek dan bahkan telah mendominasi jumlah putusan perceraian pada beberapa wilayah di Indonesia. Persoalan putusan verstek pada perkara perceraian (cerai gugat) akhirnya akan berakibat pada hilangnya hak-hak istri karena suami tidak pernah hadir di persidangan. Lebih lanjut, istri akan kesulitan dalam menggugat nafkah untuk dirinya maupun nafkah anaknya. Penelitian normatif ini mengkaji paradigma perlindungan hukum dan keadilan para pihak dalam penyelesaian perkara perceraian dan penerapan ex officio hakim sebagai bentuk perlindungan hukum dan keadilan dalam putusan verstek perkara perceraian. Kajian tersebut dilakukan dengan menggunakan pendekatan perundang-undangan (statute approach) dan pendekatan konseptual (conceptual approach). Pengumpulan data dilakukan dengan studi kepustakaan dan studi dokumen. Hasil penelitian menyimpulkan: pertama, perlindungan hukum dan keadilan merupakan kewenangan ex officio hakim karena jabatannya untuk membantu pencari keadilan guna mendapatkan keadilan secara efektif dan efisien melalui proses peradilan. Kedua, penerapan ex officio hakim sebagai wujud perlindungan hukum dan keadilan dalam putusan verstek perkara perceraian adalah dengan mengadili di luar petitum (ultra petita) berupa menambah amar yang tidak diminta dalam petitum sebagaimana ketentuan Pasal 41 huruf c UUP No. 1 Tahun 1974 jo UU No.16 Tahun 2019. Kata Kunci: Perlindungan hukum; keadilan; ex officio; verstek perceraian